THE IMPLEMENTASION OF GUIDED DISCOVERY LEARNING TO IMPROVE STUDENTS CRITICAL THINKING SKILL IN SIMPLEÂ HARMONIC MOTION AT SENIOR HIGH SCHOOL - YUNISMA Br SEBAYANG, DWIGA (Inovasi Pendidikan Fisika, 2017)
Students critical thinking skills are important skills in learning. The critical thinking indicator in this research consists of 4 indicators. The result of observation in SMA Negeri 18 Surabaya shows only one indicator has been achieved that is the interpretation . For that purpose, the research is related the application of guided discovery learning to describe the implementation of learning, improvement of critical thinking skill, and students response to simple harmonic motion. This research uses experimental method with pre-experimetal design and type of this research is one group pre-test post-test design using one experiment class and two replication classes. The implementation of the three classes observed from the teacher activity for two meetings was stated to be very well executed. Based on the analysis of n-gain, critical thinking skills in the experimental class and the replication class 1 increased with high category while in the replication class 2 increased with medium category. The learning proces get positive response from the students with very good category. The critical thinking skill that gets the lowest increase is the analysis. Overall learning by applying the guided discovery model can improve students critical thinking skills.   Key word: guided discovery learning, critical thinking skill, simple harmonic motion